Metapangenomic investigation provides insight into niche differentiation of methanogenic populations from the subsurface serpentinizing environment, Samail Ophiolite, Oman - Thieringer, Patrick H.; Boyd, Eric S.; Templeton, Alexis S.; Spear, John R. (Frontiers in Microbiology, 2023)
Serpentinization reactions produce highly reduced waters that have hyperalkaline pH and that can have high concentrations of H2 and CH4. Putatively autotrophic methanogenic archaea have been identified in the subsurface waters of the Samail Ophiolite, Sultanate of Oman, though the strategies to overcome hyperalkaline pH and dissolved inorganic carbon limitation remain to be fully understood. Here, we recovered metagenome assembled genomes (MAGs) and applied a metapangenomic approach to three different Methanobacterium populations to assess habitat-specific functional gene distribution. A Type I population was identified in the fluids with neutral pH, while a Type II and "Mixed" population were identified in the most hyperalkaline fluids (pH 11.63). The core genome of all Methanobacterium populations highlighted potential DNA scavenging techniques to overcome phosphate or nitrogen limitation induced by environmental conditions. With particular emphasis on the Mixed and Type II population found in the most hyperalkaline fluids, the accessory genomes unique to each population reflected adaptation mechanisms suggesting lifestyles that minimize niche overlap. In addition to previously reported metabolic capability to utilize formate as an electron donor and generate intracellular CO2, the Type II population possessed genes relevant to defense against antimicrobials and assimilating potential osmoprotectants to provide cellular stability. The accessory genome of the Mixed population was enriched in genes for multiple glycosyltransferases suggesting reduced energetic costs by adhering to mineral surfaces or to other microorganisms, and fostering a non-motile lifestyle. These results highlight the niche differentiation of distinct Methanobacterium populations to circumvent the challenges of serpentinization impacted fluids through coexistence strategies, supporting our ability to understand controls on methanogenic lifestyles and adaptations within the serpentinizing subsurface fluids of the Samail Ophiolite.